System Dynamics Simulation of Semi-Organic Fertilizer and Pest Management Scenarios to Enhance Sustainable Food Security in Bungur Village - Amanda Dian Rahmawati; Murnawan, Hery (Indonesian Journal of Engineering and Technology (INAJET), 2025)
This study investigates agricultural sustainability and food security in Bungur Village, Nganjuk Regency, East Java, by addressing critical challenges such as an aging farming population, heavy reliance on chemical fertilizers, and recurring pest infestations. To identify key determinants, Structural Equation Modelling–Partial Least Squares (SEM–PLS) was employed, while system dynamics modeling using STELLA software was applied to simulate three alternative intervention scenarios. The simulation results demonstrate that the adoption of semi-organic fertilizers increases profit by approximately 1% (Rp106.4 million), the use of environmentally friendly pest management enhances profit by 12% (Rp117.8 million), and the combined application of both strategies yields the highest improvement, with a 16% increase (Rp122.3 million) compared to the baseline condition (Rp105.6 million per hectare annually). Model reliability was confirmed through validation tests using mean comparison error (≤5%) and variance explained (≤30%). These findings highlight that integrated interventions are effective in improving productivity, profitability, and sustainability, while also providing incentives to encourage greater youth participation in agriculture. Nonetheless, the scope of this study is limited to Bungur Village and focuses exclusively on rice, shallots, and corn, without accounting for farmer-level heterogeneity. Future studies are recommended to extend the model to wider geographical contexts and incorporate factors such as climate variability and market fluctuations.